Problematics of Students Memorizing the Qur'an in Maintaining Memorization Post-Pesantren (Case Study of Ushuluddin Faculty Students, UINSU) - Mardianti, Mardianti; Nasution, Muhammad Roihan; Is, Fadhilah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Memorizing the Qur'an is not only about ziyadah, but how to maintain the memory that has been memorized. The Faculty of Ushuluddin UIN SU is one of the faculties that focuses on the Tahfiẓ Al-Qur'an program, as the content contained in the curriculum of the Faculty of Ushuluddin requires memorizing the Al-Qur'an. The purpose of this study is to find out the problems of students who memorize the Qur'an in maintaining memorization after boarding school along with solutions to maintain it. This type of research is descriptive qualitative. The results showed that the problems of students in maintaining memorization after Islamic boarding school were that most students were lazy and not consistent in dividing time, the influence of gadgets, environmental factors, and lack of motivation because there were no teachers and friends. To overcome these problems, of course, there are solutions, namely fixing the intention first, making time in muraja'ah, must be istiqamah in dividing time, reducing playing gadgets, looking for a good environment, often motivating yourself and looking for mentors and friends, and using the right muraja'ah method.